Software engineering sub-ontology for specific software development - Wongthongtham, Pornpit; Chang, Elizabeth; Cheah, Chan; Dillon, Tharam S. (IEEE, 2005)
In this paper we propose software engineering sub ontology. We called it application-specific ontology, for specific software development. It enables remote team members browsing, searching, sharing, and authoring ontological data under the distributed software engineering projects environment. We transform explicit meaningful human knowledge into application-specific ontology, where knowledge structures and semantics are linked, and we go through a formal hand-shaking agreement establishing process before the semantic contents are updated in ontology repositories. The application-specific ontology is used for communication over project agreement to facilitate better, highly consistent communications and formalized domain knowledge sharing. We assume that object-oriented development is deployed in the distributed projects. The knowledge of object-oriented development formed in the application-specific ontology clarifies the object-oriented development concepts in a machine understandable form. Software agent, for example, can be utilised to extract information.